Influence of physical exercise practice against SARS-CoV-2 (COVID-19) infection: narrative review - Pereira, Gustavo José de Sá; Canciglieri, Raphael do Santos; Fernandes, Célio Junior da Costa; Moura, Leandro Pereira de; Moura, Rodrigo Ferreira de (Open Science Journal, 2022)
As a protective measure against the Covid-19 virus, the world health organization strongly recommended social isolation. Because of a lower offer of physical exercise, there was an increase in the number of physical inactivity, poor diet, and psychological disorders. In this sense, this literature review aims to address how the practice of physical exercise is important to protect the metabolic and psychological health of the population. During forced isolation, it was possible to observe an increase in sedentary lifestyle and poor diet. As an outcome, possible damage to the population's mental health was also identified. In contrast, it was observed that individuals who practiced physical exercise, managed to mitigate both metabolic and psychological damage. Ahead, it was also possible to observe that this practice significantly contributed to the individuals' immune system, which can collaborate with the organism in the fight against possible contamination. Given this, the objective of this review was to identify possible implications of physical exercise on psychological and immunological aspects in coping with Covid-19. Important physiological effects of exercise were found, such as elevation of the brain-derived neurotrophic factor (BDNF), which has beneficial effects in controlling depression and cognitive performance; the control of obesity through specific training methodologies can collaborate to control pro-inflammatory cytokines and increase mitochondrial function and immune system. In addition, there are up to 205 symptoms after infection by SARS-CoV2 and physical exercise can be a great ally for recovery. Therefore, it is believed that regular exercise has positive effects before, over, and post-pandemic.